Economic Analysis of Pavement Preservation Techniques. Issue 12 (December 2018) - Zuniga-Garcia, Natalia; Martinez-Alonso, Wilfrido; de Fortier Smit, Andre; Hong, Feng; Prozzi, Jorge A.
This paper summarizes the research study conducted to develop and implement a methodological framework, using an economic analysis technique, to evaluate the cost effectiveness of the three different preventive maintenance treatments applied to roadways in Texas: chip seals, microsurfacing, and thin overlays. The analysis is based on a stochastic evaluation of the effective life and cost of more than 14, 000 maintenance and rehabilitation projects undertaken from 1994 to 2015. The effect of traffic loads, traffic volume, and roadway type was also evaluated. The life-cycle cost of the preventive maintenance techniques was obtained using a Monte Carlo simulation. Among the principal results, it was found that chip seals are the most cost-effective treatment and present the lowest life-cycle cost variability. The effective life of all three treatments was found to be quite similar. Additionally, it was found that the chip seals and microsurfacing tend to present comparable life-cycle costs when used on heavy traffic roadways.